Multiple Domains in the Kv7.3 C-Terminus Can Regulate Localization to the Axon Initial Segment - Hefting, Louise Leth; D’Este, Elisa; Arvedsen, Emil; Benned-Jensen, Tau; Rasmussen, Hanne Borger (Frontiers in Cellular Neuroscience, 2020)
The voltage-gated Kv7.2/Kv7.3 potassium channel is a critical regulator of neuronal excitability. It is strategically positioned at the axon initial segment (AIS) of neurons, where it effectively inhibits repetitive action potential firing. While the selective accumulation of Kv7.2/Kv7.3 channels at the AIS requires binding to the adaptor protein ankyrin G, it is currently unknown if additional molecular mechanisms contribute to the localization and fine-tuning of channel numbers at the AIS. Here, we utilized a chimeric approach to pinpoint regions within the Kv7.3 C-terminal tail with an impact upon AIS localization. This strategy identified two domains with opposing effects upon the AIS localization of Kv7.3 chimeras expressed in cultured hippocampal neurons. While a membrane proximal domain reduced AIS localization of Kv7.3 chimeras, helix D increased and stabilized chimera AIS localization. None of the identified domains were required for AIS localization. However, the domains modulated the relative efficiency of the localization raising the possibility that the two domains contribute to the regulation of Kv7 channel numbers and nanoscale organization at the AIS.